Soil coverage and apple tree growth on the establishment of an orchard under organic production system Coberturas do solo e crescimento da macieira na implantação de um pomar em sistema orgânico de produção - Pelizza T.R. (2009)
Soil cover is one of the options for weed management in the orchard but this might affect fruit trees development. The objective of this work was to evaluate apple trees growth during the orchard establishment stage by using different materials and soil cover plants. The experimental apple orchard was planted in 2003, in Vacaria, RS, Southern of Brazil, with the cv. Galaxy managed under organic system. The experiment followed the randomized block design, with three replications. The treatments were applied in the tree rows, as follows: control (without weed management), manual weeding, black plastic film, black net, pinus sawdust, pinus needle mulch, Andropogon sp mulch, annual ryegrass (Lolium multiflorum), black oat (Avena strigosa), black oat + common vetch (Vicia sativa), black oat + fodder radish (Raphanus sativus), annual ryegrass + white clover (Trifolium repens) + spontaneous plant cover, weed mowing. The soil covered by weeds was monthly measured, during the spring/summer season, over the second and third years of the orchard establishment, and this was related to the apple trees growth. The treatments with manual weeding, black plastic film, pinus needle and Andropogon mulch maintained the soil cover by weeds below 20%. The apple tree height and diameter decreased with the increase of soil cover by weeds, reflecting weeds competition with apple trees.